Trust not in money: The effect of financial conflict of interest disclosure on dietary behavioural intention - Goodwin, R.; Mullan, Barbara (Emerald Group Publishing Limited, 2009)
Purpose – The purpose of this paper is to determine the impact of financial conflict of interest (FCI) disclosure on dietary behavioural intention related to the Glycaemic Index (GI) of food. Design/methodology/approach – A total of 72 participants were randomly allocated to two conditions by reading an academic journal article about GI that contained an FCI disclosure (conflict) or a statement detailing that the authors had no FCI to declare (no-conflict). Using a questionnaire, participants made judgements about the article and authors as well as intention to perform GI-related behaviour. These were then analysed for significant differences between the two conditions. Findings – Although no significant differences emerged between group means of judgements about the article, those in the conflict condition judged the authors as being significantly less trustworthy and credible than those in the no-conflict condition. Contrary to expectation, those in the conflict condition reported significantly higher intentions to perform GI-related behaviour. Research limitations/implications – The present research must be conducted in other populations of interest in order to establish whether the results can be generalised. Practical implications – The results suggest that FCI disclosure might be best placed at the beginning of articles and that education about FCI be made available to the general public. Originality/value – The paper examines the practical implications of FCI disclosure. It also focuses on a readership beyond an academic community who is well acquainted with the subject area and issues pertaining to FCI.